Analisis Customer Lifetime Value Berdasarkan Produk Menggunakan Metode RFM/P dan Algoritma Fuzzy C-Means - Rachmawati, Dyana; Monalisa, Siti; Muttakin, Fitriani (Building of Informatics, Technology and Science (BITS), 2024)
212 Mart Soebrantas is a retail company based on a Sharia Cooperative. 212 Mart Soebrantas segments its customers in terms of monetary value, specifically customers who make many purchases. Currently, 212 Mart does not consider recency and frequency, because customers who make transactions of 50 thousand rupiahs receive 1 point. If the points accumulate to 200, they exchange them for a shopping voucher worth 50 thousand rupiah to shop at 212 Mart. 212 Mart Soebrantas needs to understand Customer Lifetime Value (CLV) to determine the customer categories worth keeping and profitable for 212 Mart. Therefore, 212 Mart needs to understand and know its customer segments based on product-based transactions or RFM/P. This research analyzes Customer Lifetime Value Based on Products Using the RFM/P Method and Fuzzy C-Means Algorithm at 212 Mart Soebrantas to help 212 Mart identify customer segment characteristics, and customer loyalty per product category, and provide strategic recommendations. The data used is customer transaction data from January 2023 to September 2023. The study uses products from 10 categories with 6 attributes: Member Code, Stock Name, Transaction Date, Quantity, Basic Price, and Department. The research shows that the best cluster is found in the Basic Material category with a DBI value of 0.4990, and it is a Superstar Customer based on Customer Portfolio Analysis (CPA).